Listening to the Voice of People: First Iran National Health Assembly - Ali Asghar Farshad; Narges Rostamigooran; Masoud Motalebi Ghaen; Abbas Vosoogh; Roksana Mirkazemi (Shahid Beheshti University of Medical Sciences, 2019)
Background: People participation in health affairs has been gaining more importance recently. Establishment of the first National Health Assembly (NHA) was done in Iran to shape dialogue among stakeholders and  advocacy for health among all non-health sectors; decentralizing health decision making process, involving community and societies in health policy and planning, identification, appreciation, and development of health policies and measures in all economic, social, and cultural institutions of the country. Case report: In order to ensure participation of all people around the country, provincial Health Assemblies, district health assemblies and neighborhood health assemblies was formed throughout the country.  The main theme selected for the 1st NHA was "Health for All, All for Health". Conclusion: Final statement mentioned that health is a citizens' right and all people and organizations are responsible for it; therefore, cultural activities and legal support are needed for the institutionalization of social accountability for health.